To solve the equation \(3 - \frac{6}{5}x = -3\), follow these steps:
-
Isolate the term involving \(x\): \[ 3 - \frac{6}{5}x = -3 \] Subtract 3 from both sides: \[ -\frac{6}{5}x = -3 - 3 \] Simplifying gives: \[ -\frac{6}{5}x = -6 \]
-
Eliminate the negative sign: We can multiply both sides by -1: \[ \frac{6}{5}x = 6 \]
-
Multiply both sides by the reciprocal of \(\frac{6}{5}\): To solve for \(x\), multiply both sides by \(\frac{5}{6}\): \[ x = 6 \cdot \frac{5}{6} \] Simplifying gives: \[ x = 5 \]
So, the solution is: \[ \boxed{5} \]